The Encroachment of The Owners of Gravel and Sand Factories on The Lands and Its Effects : (Analytical Study) - Mazin Jalal Ahmed; Rakan Salah Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
After the fall of the former regime in Iraq, the phenomenon of encroachment on the State’s land became prevalent, and there is no doubt that this phenomenon is considered as one of the most dangerous problems facing the Iraq at the present time. Since the population increase in one hand, and the destruction that Iraq faced after 2003 in the other hand, subsequently led to an increase in the demand for buildings, housing and public facilities. Hence, the increase in demand for construction materials in general, including gravel and sand became inevitable factor, which prompted factory owners to take various methods to provide as much proportion of gravel and sand as possible. Additionally, to reap the largest profit for themselves, without predicting future dangerous risks brought to these lands, particularly agricultural lands and agricultural production in the state. The seriousness of this encroachment on the land including the erosion, drift and usurpation of quarry lands, is the justification to write our research focusing on this subject as an attempt to contribute in presenting the issues related to encroachment on state’s land by factories’ owners. We have studied the problem in the manner of an analytical study, by analyzing the legislative texts related to the subject of the study. The study was divided into three sections. In the first section (as an introductory section), we discussed the definition of gravel and sand factories and the procedures necessary to obtain a work permit. In the second section, we presented pictures of land encroachment by the owners of gravel and sand factories. In the third section, we dealt with the effects of the trespassing issued by the owners of gravel and sand factories on the lands. We also conclude the study by mentioning the most important conclusions and suggestions.